Literasi Guru Sekolah Dasar terkait Asesmen - Rizkia Suciati (Universitas Muhammadiyah Prof. Dr. HAMKA Press, 2015)
Descriptive study about assessment literacy of primary school teachers conducted to determine the extent to which literacy assessment of elementary school teachers in Bengkulu. Surveys carried out on primary school teachers (n = 28) derived from 22 primary schools from five districts as the city of Bengkulu. Respondents were asked to complete the four questions are closed and five open questions regarding the level of assessment literacy, main purposes of assessment and use of various assessment techniques, the need for further training and recommends ways to improve the literacy assessment in higher education and on teaching practices (PPL). The teachers varying levels of literacy. Summative purpose still dominates as the purpose of assessment in learning, little is done for purposes of the opinion formative assessment (development) and diagnostics. They prefer using the technique of personal communication assessment and selection tests (limited respondents), but if there are training techniques in future assessments of their choosing assessment techniques of observation.